1973
DOI: 10.1037/h0033847
|View full text |Cite
|
Sign up to set email alerts
|

Affect and altruism.

Abstract: The relationship between affect and altruism in 7-and 8-year-old middleclass white children was investigated. Children were asked to think of things that made them happy or sad, or they were assigned to control conditions. Subsequently they were given an opportunity to donate money to other children in the experimenter's absence. In accord with predictions, children who experienced positive affect gave more than control children while those who experienced negative affect gave less than controls. Girls gave mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
121
2
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(139 citation statements)
references
References 15 publications
13
121
2
3
Order By: Relevance
“…However, the causal relationship could also be reversed (Moore, Underwood, & Rosenhan, 1973;Underwood, Froming, & Moore, 1977). An experimental design would provide more insight in the direction of causality of the link between support provision and providers' wellbeing as a function of UC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causal relationship could also be reversed (Moore, Underwood, & Rosenhan, 1973;Underwood, Froming, & Moore, 1977). An experimental design would provide more insight in the direction of causality of the link between support provision and providers' wellbeing as a function of UC.…”
Section: Discussionmentioning
confidence: 99%
“…Such "automatic processing" effects may occur in a nonreflective manner and may affect our impressions of both people and objects (Schneider, Hastorf, & Ellsworth, 1980;Zajonc, 1980 Although automatic processing may account for the effect of positive mood state on behavior, it does not appear consistent with the body of re search examining the effect of negative feelings on judgments and behav ior. That is, while a positive feeling state has generally been found to in crease the probability of drawing upon positive material in memory and behaviors such as helping and generosity (Aderman, 1972;Batson, Coke, Chard, Smith, & Taliaferro, 1979;Cunningham, Steinberg, & Grev, 1980;Isen, 1970;!sen, Clark, & Schwartz, 1976;!sen & Levin, 1972;Levin & !sen, 1975;Mischel, Ebbesen, & Zeiss, 1973;Moore, Underwood, & Rosenhan, 1973;Underwood, Froming, &Moore, 1977;Weyant, 1978), the effects of negative feeling states are far more complex. Some studies suggest that in ducing negative mood states increases the likelihood of antisocial behaviors (Baron, 1972;Baron & Bell, 1975), whereas others suggest that negative affect either has no effect or increases the likelihood of positive behaviors (Carlsmith & Gross, 1969;Cialdini, Darby, & Vincent, 1973;Cialdini & Kenrick, 1976;!sen, 1970;McMillen, 1971;Mischel, Coates, & Raskoff, 1968;Mischel & Moore, 1973;D.…”
Section: Discussionmentioning
confidence: 99%
“…T. Reagan, Williams, & Sparling, 1972;J. W. Regan, 1971;Teasdale & Fogarty, 1979;Underwood, Moore, & Rosenhan, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Other work has found associations between positive emotions and desirable social behaviors such as helpfulness (Isen, 2001), generosity (Moore, Underwood, & Rosenhan, 1973), cooperativeness (Carnevale & Isen, 1986), graciousness (Emmons & McCullough, 2003), increased trust, and more integrative negotiation outcomes (Anderson & Thompson, 2004). Amabile et al (2005) found that positive affect (in a simple linear relationship) was associated with creativity in organizations, and Bono and Ilies' (2006) work suggests that leadership communication infused with positive emotion spreads positive affect to followers.…”
Section: Benefits Of Positive Emotionmentioning
confidence: 99%